2015
DOI: 10.1093/molbev/msv136
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Resequencing of Experimental Populations Reveals Polygenic Basis of Egg-Size Variation inDrosophila melanogaster

Abstract: Complete genome resequencing of populations holds great promise in deconstructing complex polygenic traits to elucidate molecular and developmental mechanisms of adaptation. Egg size is a classic adaptive trait in insects, birds, and other taxa, but its highly polygenic architecture has prevented high-resolution genetic analysis. We used replicated experimental evolution in Drosophila melanogaster and whole-genome sequencing to identify consistent signatures of polygenic egg-size adaptation. A generalized line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(120 citation statements)
references
References 90 publications
3
112
0
Order By: Relevance
“…), and a generalized linear mixed model (GLMM) with binomial error structure and replicate population as a random effect (Jha et al. ). The binomial GLM model had a superior performance compared to the three other models in terms of detecting allele frequency differentiation and true discovery rate for both main effects and, importantly, the interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), and a generalized linear mixed model (GLMM) with binomial error structure and replicate population as a random effect (Jha et al. ). The binomial GLM model had a superior performance compared to the three other models in terms of detecting allele frequency differentiation and true discovery rate for both main effects and, importantly, the interaction.…”
Section: Resultsmentioning
confidence: 99%
“…To correct for this, we calculated P ‐values of permuted datasets to generate an empirical null distribution (equally overdispersed) that was subsequently used to estimate FDR of the observed data, following the procedure by Benjamini and Hochberg () (Jha et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…Economically important egg traits in chicken (yolk volume, egg weight) are known to have high heritability (Olsen and Knox, 1940;Shultz, 1953;Zhang et al, 2005). We know little about the genetic control of egg size and number in non-model animal taxa, and most of what we know comes from the common fruit fly Drosophila melanogaster, for which the egg size-number tradeoff is well-known (Mackay et al, 2012;Jha et al, 2015).…”
Section: Genetic Controls On Offspring Size and Fecundity In Animalsmentioning
confidence: 99%
“…Based on data from controlled crosses, he concluded that egg size is polygenically controlled by genes on all four chromosomes. Jha et al (2015) adopted a whole-genome resequencing approach on replicated experimental-evolution lines selected for large and small egg sizes, respectively. Corroborating Warren's findings, Jha and colleagues report that egg size is polygenically controlled by at least 200 genes.…”
Section: Genetic Controls On Offspring Size and Fecundity In Animalsmentioning
confidence: 99%
“…; Jha et al. ). Assuming that the reference population is not evolving during the experiment, this design permits the distinction between a generic adaptive response to the laboratory and adaptation to the experimental conditions of interest.…”
Section: Introductionmentioning
confidence: 98%